The effectiveness of process payment at Belati Wangsa (M) Sdn Bhd / Wan Noor Hafizah Anuar - Anuar, Wan Noor Hafizah (2011)
This study focuses on “The effectiveness of process payment at Belati Wangsa (M) Sdn Bhd”. The main objective of this research is to determine the level of effectiveness of process payment, to identify whether communications influence the effectiveness of process payment, to investigate whether organization influence the effectiveness of process payment, to determine whether operating procedures influence the effectiveness of process payment and provide recommendation to improve the process payment at Belati Wangsa (M) Sdn Bhd. Besides that, to understand the process payment at Belati Wangsa (M) Sdn Bhd researcher also studies the procedures of process payment in this company. This report outlining the introduction, literature review, findings and analysis, conclusions and recommendations based on the journal and observation during practical trainee at Belati Wangsa (M) Sdn Bhd Ipoh Perak.